THE IMPACT OF TIKTOK SOCIAL MEDIA USE ON THE POLITENESS BEHAVIOR OF FIFTH GRADE STUDENTS AT PALEMBANG CITY ELEMENTARY SCHOOL - Sinta Bela; Yasir Arafat; Wahid Ibrahim B.N (Cerdas Proklamator, 2026)
This study aims to determine and describe the impact of TikTok social media use on the politeness behavior of fifth grade students at SDN 30 Palembang. The background of this study is based on the increasing use of social media among elementary school students which potentially affects student behavior, especially in terms of politeness. This research used a qualitative approach with a descriptive method. The subjects of this study were 20 fifth grade students of SDN 30 Palembang. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing, while data validity was tested through source and method triangulation. The results showed that the use of TikTok social media had an impact on students’ politeness behavior, including changes in language use that became less polite, decreased learning concentration, reduced social interaction ethics, and low self-control in using social media. However, TikTok also had positive impacts, such as increasing students’ creativity and broadening their knowledge when used wisely. Therefore, the role of teachers, parents, and schools is very important in guiding and supervising students in using social media wisely while maintaining politeness values and positive character.